Increasing consumer engagement through gamification in marketing campaigns - Ismail Razak (SEAN Institute, 2024)
Gamification is a strategy that integrates game elements into non-game contexts with the goal of motivating, engaging, and increasing user participation. Successful marketing campaigns not only attract attention but also build deeper interactions with consumers. This research aims to explore and analyze the impact of implementing gamification elements in marketing campaigns on consumer engagement. This research uses a qualitative approach with descriptive methods. The research results show that the application of gamification in marketing campaigns is effective in increasing consumer engagement. A qualitative approach in understanding the target audience provides a solid foundation for designing relevant game concepts, while the integration of technology such as artificial intelligence provides a more personalized gamification experience. Attractive prizes and promotions effectively motivate participation, and two-way communication strengthens consumer engagement. Regular evaluation and rapid response to consumer feedback fosters continuous improvement, while building an online community creates a collaborative space that supports interaction between consumers. Overall, gamification strategies not only create engaging marketing experiences but also build sustainable and meaningful relationships between brands and consumers in today's digital marketing environment.